ISLAMIC RELIGIOUS EDUCATION AS A MEANS TO ACHIEVE SOCIAL JUSTICE FOR MINORITY GROUPS - Irfan Aziz; Habib Anwar Al Anshori (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This investigation explores the strategic function of Islamic Religious Education in materializing social equity for minority segments in Indonesia. Through qualitative methodology utilizing library research approach, this study analyzes theoretical construction of social justice from Islamic perspective and its implementation within educational contexts. Findings indicate that Islamic Religious Education possesses substantial potential as social transformation instrument through developing inclusive and justice-founded learning models. Complexity of identified challenges encompasses structural barriers, pedagogical competency limitations, and cultural resistance. Minority community empowerment strategies necessitate multidimensional approaches integrating transformative education principles, critical pedagogy, and culturally responsive teaching. The justice-founded Islamic ReligiousEducation model formulated accentuates developing diversity-sensitive curricula, student- centered learning methodologies, and comprehensive evaluation systems. Implementation of this model requires long-term commitment from all educational stakeholders to create authentically inclusive and equitable learning environments. This research contributes theoretical frameworks and practical strategies for enhancing Islamic Religious Education's effectiveness in promoting social equity and minority rights within Indonesia's diverse educational landscape.